General pharmacological studies on Biapenem - Shiba, Toshiharu; Shikata, Yoshiyuki; Ishikawa, Tomokazu; Yanaka, Masao; Kitazumi, Kazuhiro; Ito, Mami (CHEMOTHERAPY, 1994)
General pharmacological properties of biapenem (BIPM), a new carbapenem antibiotic, were studiedand the following results were obtained. 1. BIPM at doses of 10-1000mg/kg i.v. caused no influences on the gross behavior of mice.Neither 30 nor 100 mg/kg i.v. of BIPM affected the spontaneous motor activity, thiopental-induced hypnosis and pentylenetetrazole strychnine-and electroshock-induced convulsive reactions in mice. Furthermore, the same doses of BIPM showed no effects on normal body temperature and pressure-pain threshold in the inflamed paw of rats. BIPM at a dose of 300 mg/kg i.v. had no influences on the spontaneous EEG pattern in rabbits and at doses up to 600 mg/kg i.v. had no potentiation of pentylenetetrazole-induced convulsive activity in mice. In addition, intracerebroventricular injection of BIPM at doses up to 300 μg/animal did not produce behavioral changes in mice. By contrast, imipenem/cilastatin sodium at a dose of 150/150 mg/kg i.v. and above potentiated the pentylenetetrazole-induced convulsive activity and imipenem injected intracerebroventricularly at a dose of 10 μg/animal and above elicited convulsive behaviors in mice. 2. BIPM at a dose of 100 mg/kg i.v. slightly caused a decrease followed by a increase in blood pressure and increases in heart rate and femoral arterial blood flow without any changes in ECG and respiratory movement in anesthetized dogs, whereas this compound at a dose of 30 mg/kg i.v. elicited no effects on parameters. BIPM at a concentration of 10 -4M exerted no influences on contractile force, beating rate and coronary flow of isolated perfused rat hearts. 3. BIPM at a concentration of 10-4 g/ml (2.9 × 10-4M) did not influence the spontaneous motility and the contractile responses induced by acetylcholine, histamine, serotonin and barium chloride of isolated guinea pig ileums. Furthermore, BIPM at doses up to 100 mg/kg i.v. showed no effects on propulsion of gastrointestinal tract in mice and on airway resistance in anesthetized guinea pigs. 4. BIPM at doses up to 100mg/kg i.v.showed no influences on urine volume and Na+, K+and Cl-excretion in rats. A delay of BSP excretion in rats were observed at 100 mg/kg i.v. of BIPM, but notat 30 mg/kg i. v. 5. BIPM at a concentration of 10-4M did not influence the platelet aggregation by ADP and collagen, the plasma coagulation and the hemolysis test in rabbits. These findings suggest that BIPM seems to be much less potent than imipenem/cilastatin sodium in inducing proconvulsive activity and has no remarkable adverse actions regarding this general pharmacological study.